Threats to Civilians in a Global Security Environment: Selected Aspects - Żebrowski, Andrzej; Szkurłat, Izabela (Roczniki Nauk Społecznych, 2024)
The human environment is a co-opting of positive and negative threats, accompanied by a war of nerves. The evolving and dynamically changing security space of individual states is the source of many complex threats with diverse backgrounds. They very often overlap, which means that they are difficult to identify and combat. They occur in non-military as well as military spheres. Their multifaceted nature means that particular aspects may dominate, if not at the beginning of a particular situation, then they will emerge during. However, it should always be borne in mind that political threats will predominate. It is also important that the emergence of one threat entails another. Particularly dangerous are the natural and deliberate threats associated with negative human activities that threaten both him and his environment. He has at his disposal a wide range of tools to carry out destructive activities. Knowledge of the risks and their monitoring allows anticipatory measures to be taken to minimise the loss of resources.